Industrial Practices in Repair, Maintenance, and Performance Evaluation of three-Phase Induction Motors: A Practical Case Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Repair and rewinding of three-phase induction motors is a routine but technically demanding activity in industrial maintenance workshops, and the quality of that work has a direct bearing on motor efficiency, reliability, and service life. While international standards (e.g., IEEE 43, IEC 60034 series, NEMA MG-1, ISO 21940-11) define acceptance criteria for insulation resistance, surge/impulse withstand, and rotor balancing, published literature rarely documents how these criteria are applied together on a single motor as it moves through a workshop repair cycle. This paper addresses that gap through a practical case study of a burnt-out three-phase induction motor processed at an industrial motor-servicing facility.The objective of the study is to document, in a structured and reproducible format, the diagnostic and corrective sequence applied to the motor — direct current resistance (DCR) testing, insulation resistance (Megger) testing, surge testing, rotor static and dynamic balancing, mechanical reconditioning, and stator rewinding — and to compare the pre-repair (faulty) and post-repair (healthy) results against recognised acceptance limits. The motor was diagnosed with a grounded, turn-to-turn shorted stator winding (Megger reading of 0 MΩ and a shorted phase pair) and unbalance readings far above the workshop's 9 g acceptance threshold. Following stripping, rewinding with Class F insulation and vacuum-pressure impregnation (VPI), and two-plane dynamic balancing, the motor achieved an insulation resistance of 998–1000 MΩ, a maximum inter-phase DCR deviation of 0.2 Ω, superimposed surge waveforms across all three phases, and a final rotor unbalance below 9 g on both correction planes.The novelty of this work lies in presenting a single, fully-instrumented before/after case record that links electrical diagnostics, mechanical balancing, and winding-design considerations (coil pitch, connection type) within one workshop cycle, and in framing the acceptance criteria used against established international standards rather than workshop convention alone. The findings are intended to serve as a practical reference for motor-repair technicians, junior engineers, and students, and as a template for reporting repair-quality data in a form suitable for later statistical or predictive-maintenance analysis.